Performance of the pattern‐based interpretation of p53 immunohistochemistry as a surrogate for TP53 mutations in vulvar squamous cell carcinoma. Issue 1 (7th June 2020) - Kortekaas, Kim E; Solleveld‐Westerink, Nienke; Tessier‐Cloutier, Basile; Rutten, Tessa A; Poelgeest, Mariëtte I E; Gilks, C Blake; Hoang, Lien N; Bosse, Tjalling
Abstract : Aims: The most commonly mutated gene in vulvar squamous cell carcinoma (VSCC) is TP53 and its prognostic value, particularly in HPV‐independent VSCC, is uncertain. In other tumours, p53 immunohistochemistry (IHC) is an excellent surrogate marker for TP53 mutations. In order to study this in VSCC, we assigned six p53 IHC patterns into two final classes: 'wild‐type' or 'mutant'. We determined the performance and interobserver variability of this pattern‐based p53 IHC approach. Methods and results: Two experienced gynaecological pathologists scored the predefined p53 IHC patterns of 59 VSCC, independently and blinded for molecular data. Agreement was calculated by Cohen's kappa. All disagreements regarding p53 IHC patterns were resolved by a consensus meeting. After DNA isolation, the presence of pathogenic TP53 variants was determined by next‐generation sequencing (NGS). Sensitivity, specificity and accuracy of p53 IHC as a surrogate marker for TP53 mutation status were calculated. Initial p53 IHC pattern interpretation showed substantial agreement between both observers ( k = 0.71, P < 0.001). After consensus, 18 cases (30.5%) were assigned a final p53 IHC class as TP53 wild‐type and 41 cases (69.5%) as mutant. The accuracy between the p53 IHC class and TP53 mutation status, after the consensus meeting, was 96.6%. Moreover, the sensitivity and specificity were high 95.3% [95% confidence interval (CI) = 82.9–99.1% and 100% (95% CI = 75.9–100%)]. Conclusions: Pattern‐based p53 IHC classification is highly reproducible among experienced gynaecological pathologists and accurately reflects TP53 mutations in VSCC. This approach to p53 IHC interpretation offers guidance and provides necessary clarity for resolving the proposed prognostic relevance of final p53 IHC class within HPV‐independent VSCC.